Autoeficácia para a prática de atividade física por indivíduos adultos - De Barros, Mariana Bennaton (2012)
Self-efficacy to regular practice of physical activity (PA) can be defined as the ability to keep practicing exercises even with some obstacles that could appear. It is constituted through the influence of 4 main sources: mastery experiences, vicarious experiences, social persuasion and physiological and affective states. The aim of the study was to measure the level of self-efficacy to the regular practice of PA, its construction sources and correlate the level of self-efficacy with each one of the sources. An amount of 196 practitioners of PA took part in this study. The results showed that the level of self-efficacy was 111.19 points in scale that can range from 18 to 162 points. The most prominent source in the construction of self-efficacy was the social persuasion, with an average of 27.64 points in scale that can range from 4 to 36 points. For the correlations, it was used the Pearson coefficient (r). Mastery experiences stood out among the other sources (r = .30). The results agree with the literature, establishing the importance of the encouragement of close people in the maintenance of the behavior to practice PA, as well as to observe positive models, success experiences and feel comfortable during the exercises. © FTCD/FIP-MOC.